Within-Subject Variability in Repeated Measures of Salivary Analytes in Healthy Adults - Thomas, Mark V. (2009)
BACKGROUND: Saliva contains a large number of biomolecules, some of which have putative diagnostic usefulness. A potential problem with the use of biomolecules in diagnosis is day-to-day fluctuation due to within-subject variability. This study evaluated the intraindividual variability of six salivary analytes in healthy adults and determined their normal range. METHODS: Unstimulated whole saliva (5 ml) was collected every 2 to 3 days on six occasions from 30 subjects in good oral and systemic health. Four of the samples were collected in the clinic, and two were collected by the subject at home. The concentration ranges of interleukin (IL)-1β, IL-6, matrix metalloproteinase-8, prostaglandin E(2), tumor necrosis factor-alpha, interferon-alpha, and albumin were examined. Descriptive statistics were computed, and a one-way random-effects model was used to quantify within- and between-subject components of variability. Intraclass correlation coefficients (ICCs) were calculated for each subject/analyte combination. RESULTS: Within-subject coefficients of variation for these analytes ranged from 67.6% to 172.1% for the in-clinic samples and from 111.9% to 201.0% for the at-home samples. The ICC for the various analytes ranged from 41% to 61% for the in-clinic samples. The at-home samples exhibited significantly more variability than did those obtained in the clinic under supervision. CONCLUSIONS: There was marked within-subject variation in the salivary concentrations of these analytes. With increased interest in salivary diagnostics, the within-subject variability, normal range, and threshold levels for abnormal levels of individual salivary analytes need to be determined if these diagnostics tests are to have clinical usefulness.